FACTORS AFFECTING FARMER'S CLIMATE RISK PERCEPTION IN DEVELOPED AND DEVELOPING COUNTRIES : EVIDENCE FROM SWITZERLAND AND GHANA - Rokhani Rokhani; Ahmad Asrofi; Ahmad Fatikhul Khasan (University of Jember, 2020)
Climate change is the primary challenge of agricultural production in developing and developed countries. Farmers' perception of climate change is the critical driver in encouraging farmers to take autonomous adaptation practices. Thus, this study aimed to identify factors affecting farmers' perception of climate change in developing and developed countries and take Ghana and Switzerland as the study cases. The study used data from 378 cocoa farmers in Ghana and 109 farmers in Switzerland. The data was obtained from a structured interview and survey and contained socio-economic and farm characteristics of farmers. This study employed an ordered probit regression to estimate the factors affecting farmers' perception of climate change. The results show that landholding, farm income, and education significantly affect farmer perception of climate change. Landholding and farm income significantly affect farmer perception of climate change in Switzerland and Ghana. But, education only significantly affects the farmers' perception of climate change in Switzerland. Meanwhile, age and crops/livestock ownership does not significantly affect farmers' perception of climate change in Ghana and Switzerland. The results also show that Switzerland's farmers have a stronger perception of climate change than farmers in Ghana. Keywords: climate risk perception, climate change perception, Ghana, Switzerland